2012
DOI: 10.1002/ange.201201244
|View full text |Cite
|
Sign up to set email alerts
|

A Bulky Biaryl Phosphine Ligand Allows for Palladium‐Catalyzed Amidation of Five‐Membered Heterocycles as Electrophiles

Abstract: Palladium-catalyzed amidation of five-membered heterocyclic bromides that contain multiple heteroatoms was achieved for the first time using the Pd/1 catalyst system. This system allows for efficient access to N-arylated imidazoles, pyrazoles, thiazoles, pyrroles, and thiophenes in moderate to excellent yield. Experimental results and DFT calculations point to the need for electron-rich and especially sterically demanding biaryl phosphine ligand to promote these difficult cross-coupling reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…[12] In particular, the transformation of five-membered heterocycles bearing more than one heteroatoms, such as pyrazoles and imidazoles, has proven to be challenging. [13,14] Thus, the development of a catalyst system capable of facilitating the coupling of a diverse range of heteroaryl and functionalized substrates under mild reaction conditions is still highly desirable. Herein, we report a general catalyst system based on a palladacycle precatalyst ligated by dialkylbiarylphosphine ligand L3 (XPhos) for the palladium-catalyzed Negishi cross-couplings at ambient temperature or with low catalyst loadings.…”
mentioning
confidence: 99%
“…[12] In particular, the transformation of five-membered heterocycles bearing more than one heteroatoms, such as pyrazoles and imidazoles, has proven to be challenging. [13,14] Thus, the development of a catalyst system capable of facilitating the coupling of a diverse range of heteroaryl and functionalized substrates under mild reaction conditions is still highly desirable. Herein, we report a general catalyst system based on a palladacycle precatalyst ligated by dialkylbiarylphosphine ligand L3 (XPhos) for the palladium-catalyzed Negishi cross-couplings at ambient temperature or with low catalyst loadings.…”
mentioning
confidence: 99%
“…To further study the reaction mechanism, control experiments were carried out (Scheme S1, more details, please see SI). These results suggested that NH 4 Br might not only served as the electrolyte, but also act as a reactant to provide the bromide anion for this one pot transformation. Moreover, it also demonstrated that the 2-phenylimidazo[1,2-a]pyridine (6) might be the intermediate in this reaction.…”
Section: Electrochemical Synthesis Of 3-bromoimidazo[12-a] Pyridinesmentioning
confidence: 94%
“…[3] Meanwhile, halogenated imidazo[1,2-a]pyridines are important blocks and versatile synthons, which could be further transformed to more complex 3-substituted imidazo[1,2-a] pyridines through cross coupling reactions. [4] To date, the preparation of these halogenated compounds has been generally accomplished in two steps: the build-up of the imidazo [1,2-a]pyridine core and the halogenation. [5] Nevertheless, the existing few methods for one pot direct synthesis of 3-halogensubstituted imidazo[1,2-a]pyridines suffered from one or more disadvantages, such as limited substrate scope, [6a] the involvement of transition-metal, [6c,d] elevated temperature [6b-d] or microwave conditions.…”
Section: Electrochemical Synthesis Of 3-bromoimidazo[12-a] Pyridinesmentioning
confidence: 99%
“…This difficulty is due partly to the different electronic properties of heterocyclic compounds, as well as to the presence of heteroatoms capable of binding to the transition metal center, thus leading to catalyst deactivation and decomposition 12. In particular, the transformation of five‐membered heterocycles bearing more than one heteroatoms, such as pyrazoles and imidazoles, has proven to be challenging 13. 14 Thus, the development of a catalyst system capable of facilitating the coupling of a diverse range of heteroaryl and functionalized substrates under mild reaction conditions is still highly desirable.…”
Section: Methodsmentioning
confidence: 99%